Literature Review: Analysis of Factors Influencing Teamwork on Team Performance in Software Development Within the Telecommunication Industry in The Middle East Region - Rahman, Fatmawati A; Rosmaladewi; Ramlah, St (International Humanity Advance, Business & Sciences, 2024)
Software in the telecommunications industry plays a crucial role in developing network systems and providing better services to customers. Software development is a complex activity relying on human commitment. Effective software development requires an experienced team, and the influence of a team in software development within the knowledge-based organization can support software companies to become more innovative and proficient. This research focuses on the Middle East region due to its significance as a center for global events and its sensitivity in strategic, political, economic, cultural, and religious aspects. The aim of this study is to examine the factors influencing team performance in software development within the telecommunications industry. The research method used is a qualitative research method utilizing secondary data sources obtained from various international journals, articles, and previous studies analyzed by the author related to the issues to be examined in this research. Overall, the implications of these findings underscore the importance of human resource management in considering cohesive factors, coordination, communication, mutual support, efforts, and contributions in building an effective teamwork environment